A chromosome-level genome assembly of the redfin culter (Chanodichthys erythropterus) - Shihu Zhao; Xiufeng Yang; Bo Pang; Lei Zhang; Qi Wang; Shangbin He; Huashan Dou; Honghai Zhang (Scientific Data, 2022)
Measurement(s) whole genome sequencing Technology Type(s) Oxford Nanopore Sequencing Sample Characteristic - Organism Chanodichthys erythropterus